Entrepreneurship and Digital Innovation: Adoption of Artificial Intelligence (AI) in French Family Business Firms - Adil ElMadhi; Malika Ait Nasser (Journal of Management Practices, Humanities and Social Sciences, 2024)
The study examines a major emphasis on investigating how training contributes to the growth of digital innovation in family businesses. The goals and prerequisites for entrepreneurial education need to be reevaluated in light of the significantly changed entrepreneurial landscape brought about by the dynamic character of the digital age and the ongoing digitization of business models. This change is necessary to bring educational strategies into line with the burgeoning digital reality of entrepreneurship. The main objective of the study is to investigate the impact of entrepreneurial passion on digital innovation within family-owned enterprises, with a unique focus on modifying the adoption of Artificial Intelligence (AI) and examining the mediating role of perceived family support. Data were collected from 150 owners/CEOs of family business firms located around Paris through an online survey employing a longitudinal study design. The study spans three-time points: Time 1 data, collected in June 2023, captures demographics, entrepreneurship education, and entrepreneurial passion. Time 2 data, gathered in July 2023, explores perceived family support and the adoption of AI. Finally, time 3 data, collected in August 2023, centres on digital innovation within family businesses. The Smart PLS method is employed for data analysis, with a comprehensive questionnaire administered through online surveys. The findings from this study offer valuable insights into the nuanced relationships between entrepreneurial passion, AI adoption, perceived family support, and digital innovation, contributing to the growing body of knowledge in the field of family business research.